A Bibliometric Analysis of the Internet of Everything in Business in 2012 - 2022 - Fitriastuti, Lucia Ika; Vemberi, Yohannes (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
The Internet of Everything (IOE) plays a vital role in the business field in the current era of digitalization. The Internet of Everything (IOE) is a combination of 4 main elements, namely people, processes, data, and objects, that make network connections more valuable. In this article, researchers present an analysis of various studies related to the Internet of Everything (IoE) in Business over the last ten years. Bibliometric analysis was used to analyze 280 articles published from 2012 to 2022. Articles will be analyzed based on the trend of the topic raised, the type of document, the name of the journal, the source of the document, the name of the publisher and even the presentation of the authors' collaboration related to IoE. The data analysis method used is bibliometric analysis. The data is imported from the Scopus database and uses Harzing's Publish or Perish applications. Meanwhile, to get data visualization, this study uses the VoS Viewer application. This study found that most articles related to the topic of IoE in Business are published more in conference proceedings than in journals, books, or book series. The most significant number of citations were articles in 2014. The highest number of publications occurred in 2021. The results of network visualization show that articles related to the Internet of Things (IoT) are the main terms or topics that are widely found related to IoE. Other related terms are Internet, Cloud Computing, Big Data, Network Security, and Social Networking (online). Implications for businesspeople can maximize the use of IoE in their business to the maximum in the current digitalization era in order to increase their business's competitive advantage. This research also shows further researchers that there are still many research opportunities related to IoE, which can be related to IoT, big data, cloud computing, and other update issues.